2004
DOI: 10.1023/b:vege.0000021680.90279.bc
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between mediterranean shrub species eight years after experimental fire

Abstract: This paper is part of a wider study in which different combinations of species were assayed for the revegetation of experimentally burnt heathlands. In this particular case, we determined whether there was any interaction between the dominant species, Erica australis, which recovered by vegetative resprouting, and the only successful woody species sown, Cytisus sp., eight years after fire and seven years after sowing. A detailed study was carried out on each square metre of cover and height of both species in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…does not seem to slow down cover by E. australis, whose mean value increases in the last sampling. However, the results recorded by Marcos et al (2004) indicate certain interference between E. australis and Cytisus spp., since a negative correlation is observed between the cover of both species eight years after burning when a more detailed analysis per square meter is carried out. Cytisus spp.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…does not seem to slow down cover by E. australis, whose mean value increases in the last sampling. However, the results recorded by Marcos et al (2004) indicate certain interference between E. australis and Cytisus spp., since a negative correlation is observed between the cover of both species eight years after burning when a more detailed analysis per square meter is carried out. Cytisus spp.…”
Section: Discussionmentioning
confidence: 90%
“…However, all these shrubs tend to branch from the base, so appear to be profusely intermixed with considerable canopy overlap. Competition among them would therefore seem likely at least for space (Marcos et al, 2004). Another aspect worth mentioning is that, in spite of the great abundance of woody species, herb cover as well as diversity (number of species) is significantly higher than in the initial situation, even 10 years after burning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, seedling establishment may have been enhanced due to an increase in free space (Bond & van Wilgen ), breaking of seed dormancy by higher soil temperatures (Tyler ; Hoffmann ; Auld & Denham ; Knox & Clarke ), and decrease in competition with dominant species (Tyler ; Laterra & Solbrig ; Marcos et al. ). Additionally, new gaps can be colonized by vegetative ramets from both the bud bank and neighbouring vegetation, since the most important regeneration strategy in these grasslands is resprouting (ca.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of shrub height difference between treatments may suggest that woody species recovery during the first year after a disturbance is mainly invested in reoccupying the bare surrounding space, in the absence of competition for light (Marcos et al 2004). Calvo et al (1998) observed that the most pronounced increase in height occurred once the shrubs have occupied practically all their initial space, achieving similar height values 9 years after treatments.…”
Section: Treatment Typementioning
confidence: 96%